AIRFOIL TYPES EFFECT ON GEOMETRY AND PERFORMANCE OF A SMALL-SCALE WIND TURBINE BLADE DESIGN - Iswahyudi, Sigit; Sutrisno, Sutrisno; Prajitno, Prajitno; Wibowo, Setyawan Bekti (Journal of Applied Engineering Science, 2020)
Many airfoils could be used to form a wind turbine blade. Different airfoil would result in altered blade planform and its performance characteristics. Airfoil identification that should be included in the design then becomes an important task. Utilizing Blade Element Momentum Theory computation procedures, eleven types of airfoils were applied in blade geometries of rotors of 2.4 m in diameters. The changes in the distribution of chord lengths, twists, solid ratio, and Reynolds numbers of the blades were compared as geometry parameters. The designed and off designed powers and thrusts were calculated, and the characteristics of the performance of the rotor were represented by the coefficient of power and coefficient of thrust. The calculated geometries showed that distinct airfoils resulted in different segments sizes of the blades and different performance characteristics of the rotors. Employing an airfoil in a blade design that has a higher lift coefficient design and higher glide ratio tend to give smaller chords sizes and solid ratio. The blade that used the airfoil also tends to have a higher coefficient of power at tip speed ratio design than that has a lower one but could be more sensitive to the changes of its rotational speeds.